2010
DOI: 10.1002/pca.1241
|View full text |Cite
|
Sign up to set email alerts
|

Determination of S‐Adenosyl‐l‐methionine in Fruits by Capillary Electrophoresis

Abstract: Fast measurements of SAM in fruits and juices are favoured by capillary electrophoresis in a 200 : 50 mm glycine : phosphate (pH 2.5) buffer system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…For each maturity stage and each tissue type, all metabolites (SAM, ACC and MACC) and enzyme activities (ACO and ACS) from the ethylene biosynthesis pathway were quantified. SAM was extracted and quantified by capillary electrophoresis (P/ACE-MDQ, Beckmann Coulter, Fullerton, CA, USA) in a glycine : phosphate buffer (300 : 50 mM, pH 2.5) as described by [51]. ACC and MACC content was measured exactly as described by [50].…”
Section: Methodsmentioning
confidence: 99%
“…For each maturity stage and each tissue type, all metabolites (SAM, ACC and MACC) and enzyme activities (ACO and ACS) from the ethylene biosynthesis pathway were quantified. SAM was extracted and quantified by capillary electrophoresis (P/ACE-MDQ, Beckmann Coulter, Fullerton, CA, USA) in a glycine : phosphate buffer (300 : 50 mM, pH 2.5) as described by [51]. ACC and MACC content was measured exactly as described by [50].…”
Section: Methodsmentioning
confidence: 99%
“…MACC was obtained after acidic hydrolysis according to Hoffman et al (1982) and also recently updated by Bulens et al (2011). SAM was extracted and quantified by capillary electrophoresis (P/ ACE MDQ, Beckman Coulter) with UV detection according to Van de Poel et al (2010). Met content was measured by gas chromatography-mass spectrometry (Agilent) as described by Oms-Oliu et al (2011).…”
Section: Ethylene and Metabolite Quantificationmentioning
confidence: 99%
“…In addition, two diastereoisomers of this compound exist, known as (S,S)-and (R,S)-S-adenosyll-methionine, among which only one has demonstrated to be biologically active (S,S-). Van de Poel et al [69] demonstrated that SAM content varies depending on food processing (relationship between heat treatment and SAM content in tomato samples is shown in Fig. 7(A,B)).…”
Section: Other Amino Acidsmentioning
confidence: 89%
“…Four degradation compounds (degradation compounds 1-4) are formed due to the heat treatment. (B) Inset showing SAM concentration (nmol/g FW) in tomato extracts during heat treatment of several hours at 75 • C. Error bars indicate the standard deviation based on two repetitions.Reprinted from[69], copyright (2010) with permission from John Wiley and Sons.…”
mentioning
confidence: 98%